State, society and communication media in the coronavirus era - Tsekeris, Charalambos; Zeri, Persefoni (The Greek Review of Social Research, 2020)
The world-historic event of the Covid-19 pandemic has once more confirmed that we live in a hyperconnected world society and that, nowadays, epidemics do not count as merely natural phenomena anymore. Instead, they should rather be viewed as disruptive events of the world society and as a man-made social catastrophe. The coronavirus pandemic has made evident the high complexity of the global system and its increased non-linear dynamics, as well as that the structural form of the world society and the national societies pertains to relational networks which variously differentiate and reproduce themselves. In such context, the present theoretical paper aims to investigate and interpret the complex relationship between the society and the coronavirus crisis, with emphasis on the role played by different forces in the field of information policy and public perceptions on Covid-19 in general. For this reason, we particularly elaborate on cultural factors, as well as on emotions like trust, responsibility and fear during the crisis. We also focus on the dynamics of contemporary media (including their cultural background) in relation to public images of the pandemic, drawing upon relevant empirical findings at international level. In overall, this casts a fresh sociological and interdisciplinary light on the current pandemic as a relational process and a digital media-driven phenomenon.